2021
DOI: 10.1007/s00535-020-01753-0
|View full text |Cite
|
Sign up to set email alerts
|

Cabozantinib in Japanese patients with advanced hepatocellular carcinoma: a phase 2 multicenter study

Abstract: Background To evaluate the efficacy and safety of cabozantinib in Japanese patients with advanced hepatocellular carcinoma (HCC) who had progressed following one or two lines of systemic therapy including sorafenib. An exploratory evaluation in sorafenib-naïve patients was performed. Methods In this open-label, single-arm, phase 2 trial, patients received oral cabozantinib 60 mg once daily. The primary endpoint was progression-free survival (PFS) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 18 publications
4
48
1
1
Order By: Relevance
“…The profile of AEs was similar to other published studies of cabozantinib. Interestingly, the rates of grade 3–4 AEs and AEs requiring dose reduction were all lower in our study than in other published trials [ 14 , 36 ]. This may reflect the differences in collection of AEs in real-life practice compared to clinical trial settings.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The profile of AEs was similar to other published studies of cabozantinib. Interestingly, the rates of grade 3–4 AEs and AEs requiring dose reduction were all lower in our study than in other published trials [ 14 , 36 ]. This may reflect the differences in collection of AEs in real-life practice compared to clinical trial settings.…”
Section: Discussioncontrasting
confidence: 84%
“…In the CELESTIAL trial, an ORR of 4% and a median OS of 10.2 months were observed with single-agent cabozantinib [ 14 ]. In another single-arm phase II trial, Kudo et al reported an ORR of 0%, DCR of 76.5%, and an OS rate at 6 months of 91.1% in 34 patients with aHCC who were mainly pretreated with sorafenib or lenvatinib, and with cabozantinib exclusively used in the second- or third-line setting [ 36 ]. Two other studies also reported the real-life use of single-agent cabozantinib [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, in June 2019, ramucirumab was approved for the treatment of HCC in patients with an AFP of ≥400 ng/mL based on positive results from the REACH-2 study [180]. In September 2020, atezolizumab plus bevacizumab was approved based on positive results from the IMbrave150 trial, and in November 2020, cabozantinib was approved based on positive results from the CELESTIAL trial [181]and briding phase 2 trial conducted in Japan [182]. Therefore, as of December 2020, approval has been granted to 1 first-line combination immunotherapy (atezolizumab plus bevacizumab), 2 second-line MTAs (sorafenib and lenvatinib) and 3 third-line agents (regorafenib [only for patients with confirmed tolerance to sorafenib] and ramucirumab [only for those with AFP ≥400 ng/mL]), which can now be used in daily clinical practice in Japan.…”
Section: Systemic Therapymentioning
confidence: 99%
“…Finally, 57 records (representing 50 trials) were included in the SLR. These 50 trials included 34 trials in the 1L setting (six single arm [30][31][32][33][34][35], six RCTs comparing against a recommended treatment or placebo [36][37][38][39][40][41][42][43], one trial with both single arm and randomized groups [44], and 26 RCTs comparing against a non-recommended treatment ) and 11 trials in the 2L setting (five single arm [71][72][73][74][75][76], five RCTs comparing against placebo [77][78][79][80][81][82], and one trial with both single arm and randomized groups [83][84][85][86]).…”
Section: Resultsmentioning
confidence: 99%